Efficacy of Stem Cell-derived Extracellular Vesicles in the Treatment of Alzheimer's Disease Model Mice: A Systematic Review and Meta-analysis - Zheng, Qinpin; Wang, Sensen; Wang, Tian; Zhang, Guirong (Current Stem Cell Research & Therapy, 2025)
BackgroundAlzheimer's disease (AD) is a neurodegenerative disease that is still incurable. Therapy with stem cell or extracellular vesicles is a promising strategy for AD treatment. Therefore, we evaluated whether stem cell-derived extracellular vesicles could improve cognitive function and pathological features in AD model mice.MethodsPubMed, Web of Science, Embase, and The Cochrane Library were searched for studies reporting stem cell-derived extracellular vesicles treatment of AD mice from the establishment of each database to 1st August 2023. SYRCLE was used to assess the risk of bias. The extracted data were analyzed using RevMan 5.4 and Stata 15 software.Results19 studies were included in the analysis. Meta-analysis showed that treatment with stem cell-derived extracellular vesicles significantly improved cognitive performance of AD mice in the Morris water maze test and the novel object recognition test, reduced β-amyloid deposition, alleviated neuroinflammation and decreased levels of the proinflammatory cytokines and glial fibrillary acidic protein (GFAP) in the brain of AD mice. However, stem cell-derived extracellular vesicle did not affect the level of brain phosphorylated tau (p-Tau).Conclusionstem cell-derived extracellular vesicles may promote the degradation of β-amyloid plaques in the brain, regulate immunity and protect nerves, which result in cognitive improvement in AD mice.
Keywords: extracellular vesicles